2022 Global report on food crises: Joint analysis for better decisions - Food Security Information Network; Vos, Rob; Rice, Brendan; Minot, Nicholas (Food and Agriculture Organization of the United Nations, 2022)
Founded by the European Union, FAO and WFP at the 2016 World Humanitarian Summit, the Global Network Against Food Crises is an alliance of humanitarian and development actors working together to prevent, prepare for, and respond to food crises and support the Sustainable Development Goal to End Hunger (SDG 2). It seeks to reduce vulnerabilities associated with acute hunger; achieve food security and improved nutrition; and promote sustainable agriculture and food systems, using a ‘3x3 approach.’ This involves working at the global, regional and national levels to support partnerships within existing structures and to improve advocacy, decision-making, policy and programming along the following three dimensions: Dimension 1 | Understanding food crises The work within this dimension aims to build greater consensus and promote evidencebased food security and nutrition analyses and reporting in order to strengthen the collection, quality and coverage of the food security and nutrition data and analysis, and inform decision-making and action. This will be achieved through the contribution to the Global Report on Food Crises, a unique ‘global public good’ under the coordination and leadership of the Food Security Information Network (FSIN), as well as the coordination, synthesis, and publication of technical analyses, including forward-looking analyses of food crises. Dimension 2 | Leveraging strategic investments in food security, nutrition and agriculture The work within this dimension aims to advocate for ‘fit for purpose’ financing that draws on the full range of resource flows (public and private, international and domestic) to better prepare for, prevent and respond to food crises. It seeks to improve coherence between humanitarian, development and peace actions (the HDP ‘nexus’) to build resilience to shocks and promote longer-term self-reliance. Activities include a strong focus on supporting capacity strengthening of country-level actors and institutions, as well as strengthening coordination at the regional level to ensure that investments are focused on the right place, at the right time. Dimension 3 | Going beyond food The work within this dimension aims to foster political uptake and coordination across clusters/sectors to address the underlying multi-dimensional drivers of food crises including environmental, political, economic, societal and security risk factors. It seeks to improve understanding and promote linkages between the different dimensions of fragility through knowledge sharing, advocacy and integrated policy responses.